Festschrift in Honor of Jerome Alan Cohen - Edwards, R. Randle (Columbia Journal of Asian Law, 1993)
The articles by Jarnie Horsley and William Afford initiate a series to be published in this and subsequent issues of the Journal of Chinese Law to celebrate Jerome Cohen’s unique role in fostering American scholarship on Chinese law. Authored by former students and academic associates, the articles will cover the spectrum from Chinese legal history to aspects of the contemporary PRC legal process. The complete series will be published separately in a festschrift volume dedicated to Cohen.